Kuss, op. 128 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Weisse, Christian Felix, 1726-1804 (poet):::Contributor:::::::::::: (B. Schott Söhne; Germany; Mainz)
First edition of the song "Ich war bey Choen ganz allein" for solo voice and piano, set to text by C.F. Weisse, also known as Der Kuss.